Multiple modes of N-type calcium channel activity distinguished by differences in gating kinetics - Delcour, AH; Lipscombe, D; Tsien, RW (The Journal of neuroscience, 1993)
In many neurons, N-type Ca2+ channels are a major Ca2+ entry pathway and strongly influence neurotransmitter release. We carried out cell- attached patch recordings (110 mM Ba2+ as charge carrier) to characterize the rapid opening and closing kinetics of N-type Ca2+ channel gating in frog sympathetic neurons. Single channels display at least three distinct patterns of gating, characterized as low-, medium- , and high-rho o modes on the basis of channel open probability (rho o) during depolarizing pulses to -10 mV. Spontaneous transitions from one mode to another are infrequent, with an exponential distribution of dwell times and mean sojourns of approximately 10 sec in each mode. Thus, a channel typically undergoes hundreds or thousands of open- closed transitions in one mode before switching to a different mode. Transitions between modes during a depolarization were occasionally detected, but were rare, as expected for infrequent modal switching. Within each mode, the activation kinetics were well described by a simple scheme (C2-C1-O), as previously reported for other types of Ca2+ channels. Rate constants are strikingly different from one mode to another, giving each mode its own characteristic kinetic signature. The gating behavior at -10 mV ranges from brief openings (approximately 0.3 msec) and long closures (10–20 msec) for low-rho o gating to long openings (3 msec) and brief closures (approximately 1 msec) for high- rho o gating. Intermediate values for mean open durations (approximately 1.5 msec) and mean closed durations (approximately 3 msec) were found for medium-rho o gating. In addition to being kinetically distinct, channel openings in the low-rho o mode often exhibit a unitary current approximately 0.2 pA larger than in the medium- or high-rho o mode. Each mode is characterized by its own voltage dependence: activation occurs at relatively negative potentials and is most steeply voltage dependent in the high-rho o mode, while activation requires very strong depolarizations and is weakly voltage dependent in the low-rho o mode. The proportion of time spent in the individual modes varies greatly from one patch to another, suggesting that modal gating may be subject to cellular control.